Perbedaan Model Altman Z-Score, Springate, dan Zmijewski dalam Memprediksi Kebangkrutan pada Sub Sektor Perdagangan Eceran yang Terdapat di Bursa Efek Indonesia - Fitria, Primasari; Azis, Ajeng Putri Pratiwi; Safitria, Ervita; Kalsum, Ummi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This research aims to determine whether there the different between Altman Z-Score, Springate, and Zmijewski in predicting the bankruptcy of registered retail sub-sector in Indonesia Stock Exchange with the sample of 8 companies selected at purposive sampling. This research includes the type of comparative research. The data used in this research is secondary data. Data collection method is a method of document analysis. The analytical technique used is the formula of Altman Z-score model, Springate model, and Zmijewski model and use Ms. Excelto processed the data. The hypotesis is done with One Way Anova via SPSS aplication. This result of this study show that based on calculations for five years, the bankruptcy prediction model of Altman Z-Score, Springate, and Zmijewski is PT. Matahari Putra Prima Tbk which has the potential to go bankrupt. The result of hypotesis show that there is a defference between Altman Z-score model, Springate model and Zmijewski model in predicting bankruptcy.